Research Status of Haplotype Assembly Technology - Wang, Jiayi (International Journal of Computer Science and Information Technology, 2024)
Haplotype, also called haploid genotype, refers to the combination of a series of variant loci located on the same chromosome. Most of the current assembly algorithms ignore the heterozygous SNP variant sites on the chromosome and assemble a pseudohaplotype sequence. Due to the importance of haplotypes for the treatment of diseases, the mining of pathogenic genes and other medical organisms, haplotype analysis methods have become particularly important. At present, the indirect haplotype inference technology mainly includes two types: the alignment-based haplotyping algorithm and the assembly-based haplotyping method. This paper briefly summarizes the current typical haplotype indirect regression technology, and also looks forward to the future of haplotype typing technology.